Subsistence production, markets, and dietary diversity in the Kenyan small farm sector - Davis Muthini; Jonathan Makau Nzuma; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2018)
Undernutrition and low dietary quality remain widespread problems especially among smallholder farmers in sub-Saharan Africa. Hence, the question as to how smallholder systems can be made more nutrition-sensitive is of particular relevance for research and policy. Recent studies analysed whether increasing farm production diversity may help to improve nutrition and found a positive but small effect on dietary diversity. The underlying mechanisms were not examined in detail. This paper tests the hypothesis that the effect of farm diversity on nutrition is small because production diversity is positively associated with dietary diversity from subsistence but negatively associated with dietary diversity from the market. This hypothesis is confirmed with data from Kenya, using different indicators of production diversity and dietary diversity scores at household and individuals levels. The results underline the important role of markets for smallholder diets and nutrition. Hence, strengthening markets and improving market access should be a key strategy to make smallholder systems more nutrition-sensitive.
Keywords: I15; O12; Q12; 330; nutrition-sensitive agriculture; malnutrition; food security; smallholder farmers; Africa